The diagnostic role and dynamic changes in cerebrospinal fluid neopterin during treatment of patients with primary central nervous system lymphoma - Mingying Geng; He Xiao; Jiaqi Liu; Yang Song; Ping Fu; Xing Cheng; Jinwei Zhang; Ge Wang (Cancer Medicine)
Abstract This study aimed at evaluating the diagnostic and prognostic role of neopterin (Npt) concentration in the cerebrospinal fluid (CSF) of patients with primary central nervous system lymphoma (PCNSL). Ninety‐nine patients were enrolled in this retrospective study; these included patients with PCNSL (n = 21), other brain tumors (n = 44), and inflammatory diseases (n = 34). CSF Npt concentration was measured using ELISA. Receiver operating characteristic (ROC) curve analysis was performed to assess the discriminative ability of CSF Npt concentration for the diagnosis of PCNSL. CSF Npt concentration in patients with PCNSL was significantly higher than that in patients with other brain tumors and inflammatory diseases (P < .001). On ROC curve analysis, the optimal cutoff CSF Npt level of 10.77 ng/mL for the diagnosis of PCNSL and the diagnostic yield of MRI were increased when used in conjunction with CSF Npt concentration. The CSF Npt concentrations in PCNSL patients with multiple lesions were significantly higher than those in patients with a single lesion. Changes in CSF Npt concentration were consistent with post‐treatment changes in tumor sizes. The CSF Npt concentration may be a good biomarker for the diagnosis, for monitoring of disease course, and for prognostic evaluation of patients with PCNSL.